2014
DOI: 10.1016/j.apsusc.2013.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of visible light photocatalytic activity of ZnS and CdS nanoparticles based on organic and inorganic coating

Abstract: Coating of ZnS and CdS nanoparticles with organic and inorganic materials can extend their light absorption in the visible region and their stability against photo-corrosion. Such materials could emerge as excellent photocatalysts for the elimination of pollutants from aqueous media using solar energy. In this study, PVP (polyvinyl pyrrolidone)-capped ZnS and CdS nanoparticles, ZnS/CdS and CdS/ZnS core shell nanoparticles were synthesized by microwave irradiation method and characterized using different techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…23 Soltani et al synthesized ZnS and CdS nanoparticles which extended the light absorption in the visible region and showed an increased stability against photo-corrosion. 24 Babu et al synthesized Cu/ TiO 2 core-shell nanowires with 3% Cu/TiO 2 and indicated the highest degradation rate of methyl orange. 25 Sunita et al synthesized TiO 2 /CuS core-shell nanostructures.…”
mentioning
confidence: 99%
“…23 Soltani et al synthesized ZnS and CdS nanoparticles which extended the light absorption in the visible region and showed an increased stability against photo-corrosion. 24 Babu et al synthesized Cu/ TiO 2 core-shell nanowires with 3% Cu/TiO 2 and indicated the highest degradation rate of methyl orange. 25 Sunita et al synthesized TiO 2 /CuS core-shell nanostructures.…”
mentioning
confidence: 99%
“…ZnS is a wide band gap semiconductor material (Eg=3.6 eV). It is commercially used as a phosphor and also as thin-film electroluminescence devices [11,12]. Semiconductor nanocrystals having dimensions smaller than 10 nm are also described as quantum dots [13].…”
Section: Introductionmentioning
confidence: 99%
“…Efficient photocatalytic processes have been proven to be of a great contribution in treatment of environmental deprivation. Photocatalytic oxidation of organic and biological molecules is one of the most efficient methods for alleviating the negative environmental impact of hazardous wastes and toxic pollutants in aqueous media [6,12]. The superiority of photocatalytic technique in wastewater treatment is due to its advantages over the traditional techniques such as quick oxidation, high efficiency, no formation of polycyclic products and oxidation of pollutants in the low levels [16].…”
Section: Introductionmentioning
confidence: 99%
“…The nano-carbon materials acted as electron collectors and transfer channels because of the well-known delocalized conjugated structure. Semiconductor heterojunctions such as CdS/TiO 2 , CdS/ZnO, CdS/ZnS, and CdS/C 3 N 4 have been widely reported in photocatalysis due to the promoted separation of photo-generated charges at the interface [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In addition, microporous and mesoporous silica could be used as support for dispersing CdS quantum dots [57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%